Metaphor and Comparison in the Portrait Characteristics of the Heroes of the Novel “We” as an Indicator of the Ye. Zamyatin’s Idiostyle: Cognitive-Functional Aspect - Evgenievna Kotsova, Elena; Alexandrovna Sidorova, Tatyana; Vladimirovna Zamarina, Ekaterina; Viktorovna Gurlenova, Ludmila; Nikolaevna Ivanishcheva, Olga (Opción, 2019)
The purpose of the work is to identify the use of metaphors and comparisons characterizing the appearance of the heroes of the anti-utopian novel “We” by Yevgeny Zamyatin in cognitive and functional aspects. It has been prov- en that the keywords of the thematic group “Human Appearance” and their lexical environment manifest the specificity of the individual style, includ- ing the writer’s cognitive style. The study focuses on the semantic features of metaphor and comparison in the lexical connections of the keywords of this group, as well as the knowledge formats behind these figurative means, which form the text’s conceptual structure. The specificity of the function- ing of figurative means as a mode of expressing the author’s intentions and his cognitive ability has been defined. Analysis of the metaphors and com- parisons in the text fragments containing the description of the heroes’ ap- pearances allowed revealing such features of Zamyatin’s idiostyle as the high “density” of figurative and expressive means, dominance of metaphors, epithets and comparisons among figurative means, the prevalence of semantic occasionalisms and the author’s comparisons in metaphor composition, cognitive-semantic specificity of metaphorization based on the “donor”-sphere, and the “geometricity” of figurative means characterizing the details of the appearance of the heroes. It is shown that the cognitive style’s specificity manifests itself in the actualization of con- cepts important for the writer, the formation of new conceptual meanings, usage of cognitive mechanisms in the emergence of new meanings, mix- ture of modes of world perception, re-categorization and polycategoriza- tion of text meanings, interaction of conceptual spheres, structure of new semantic models, etc. All this allows the writer to create colorful, expres- sive portrait features, express his own attitude to the characters and present an original individual picture of the world.